Et rodfæstet menneske og en hellig digter - Mortensen, Viggo (Grundtvig-Studier, 1998)
A Rooted Man and a Sacred Poet By Viggo Mortensen A Review of A.M. Allchin: N.F.S. Grundtvig. An Introduction to his Life and Work. With an afterword by Nicholas Lossky. 338 pp. Writings published by the Grundtvig Society, Århus University Press, 1997. Canon Arthur Macdonald Allchin’s services to Grundtvig research are wellknown to the readers of Grundtvig Studier, so I shall not attempt to enumerate them. But he has now presented us and the world with a brilliant synthesis of his studies of Grundtvig, a comprehensive, thorough and fundamental introduction to Grundtvig, designed for the English-speaking world. Fortunately, the rest of us are free to read as well. It has always been a topic of discussion in Denmark whether Grundtvig can be translated, whether he can be understood by anyone except Danes who have imbibed him with their mother’s milk, so to speak. Allchin is an eloquent proof that it can be done. Grundtvig can be translated and he can be made comprehensible to people who do not belong in Danish culture only, and Allchin spells out a recipe for how it can be done. What is required is for one to enter Grundtvig’s universe, but to enter it as who one is, rooted in one’s own tradition. That is what makes Allchin’s book so exciting and innovative - that he poses questions to Grundtvig’s familiar work from the vantage point of the tradition he comes from, thus opening it up in new and surprising ways. The terms of the headline, »a rooted man« and »a sacred poet« are used about Grundtvig in the book, but they may in many ways be said to describe Allchin, too. He, too, is rooted in a tradition, the Anglican tradition, but also to a large extent the tradition taken over from the Church Fathers as it lives on in the Orthodox Church. Calling him a sacred poet may be going too far. Allchin does not write poetry, but he translates Grundtvig’s prose and poetry empathetically, even poetically, and writes a beautiful and easily understood English. Allchin combines the empathy with the distance necessary to make a renewed and renewing reading so rewarding: »Necessarily things are seen in a different perspective when they are seen from further away. It may be useful for those whose acquaintance with Grundtvig is much closer, to catch a glimpse of his figure as seen from a greater distance« (p. 5). Indeed, it is not only useful, it is inspiring and capable of opening our eyes to new aspects of Grundtvig. The book falls into three main sections. In the first section an overview of Grundtvig’s life and work is given. It does not claim to be complete which is why Allchin only speaks about »Glimpses of a Life«, the main emphasis being on the decisive moments of Grundtvig’s journey to himself. In five chapters, Grundtvig’s way from birth to death is depicted. The five chapters cover: Childhood to Ordination 1783-1811; Conflict and Vision 1811-29; New Directions, Inner and Outer 1829-39; Unexpected Fulfilment 1839-58; and Last Impressions 1858-72. As it will have appeared, Allchin does not follow the traditional division, centred around the familiar years. On the contrary, he is critical of the attempts to focus everything on such »matchless discoveries«; rather than that he tends to emphasize the continuity in the person’s life as well as in his writings. Thus, about Thaning’s attempt to make 1832 the absolute pivotal year it is said: »to see this change as an about turn is mistaken« (p. 61). In the second main section of the book Allchin identifies five main themes in Grundtvig’s work: Discovering the Church; The Historic Ministry; Trinity in Unity; The Earth made in God’s Image; A simple, cheerful, active Life on Earth. It does not quite do Allchin justice to say that he deals with such subjects as the Church, the Office, the Holy Trinity, and Creation theology. His own subtitles, mentioned above, are much more adequate indications of the content of the section, since they suggest the slight but significant differences of meaning that Allchin masters, and which are immensely enlightening. It also becomes clear that it is Grundtvig as a theologian that is the centre of interest, though this does not mean that his work as educator of the people, politician, (history) scholar, and poet is neglected. It adds a wholeness to the presentation which I find valuable. The third and longest section of the book, The Celebration of Faith, gives a comprehensive introduction to Grundtvig’s understanding of Christianity, as it finds expression in his sermons and hymns. The intention here is to let Grundtvig speak for himself. This is achieved through translations of many of his hymns and long extracts from his sermons. Allchin says himself that if there is anything original about his book, it depends on the extensive use of the sermons to illustrate Grundtvig’s understanding of Christianity. After an introduction, Eternity in Time, the exposition is arranged in the pattern of the church year: Advent, Christmas, Annunciation, Easter and Whitsun. In the section about the Annunciation there is a detailed description of the role played by the Virgin Mary and women as a whole in Grundtvig’s understanding of Christianity. He finishes the section by quoting exhaustively from the Catholic theologian Charles Moeller and his views on the Virgin Mary, bearing the impress of the Second Vatican Council, and he concludes that in all probability Grundtvig would not have found it necessary to disagree with such a Reformist Catholic view. Finally there are two sections about The Sign of the Cross and The Ministry of Angels. The book ends with an epilogue, where Allchin sums up in 7 points what modem features he sees in Gmndtvig. Against the fragmented individualism of modem times, he sets Gmndtvig’s sense of cooperation and interdependence. In a world plagued with nationalism, Gmndtvig is seen as an example of one who takes national identity seriously without lapsing into national chauvinism. As one who values differences, Grundtvig appeals to a time that cherishes special traditions. Furthermore Gmndtvig is one of the very greatest ecumenical prophets of the 19th century. In conclusion Allchin translates »Alle mine Kilder« (All my springs shall be in you), »Øjne I var lykkelige« (Eyes you were blessed indeed) and »Lyksaligt det Folk, som har Øre for Klang« (How blest are that people who have an ear for the sound). Thus, in a sense, these hymns become the conclusion of the Gmndtvig introduction. The point has been reached when they can be sung with understanding. While reading Allchin’s book it has been my experience that it is from his interpretation of the best known passages and poems that I have learned most. The familiar stanzas which one has sung hundreds of times are those which one is quite suddenly able to see new aspects in. When, for example, Allchin interprets »Langt højere Bjerge« (Far Higher Mountains), involving Biblical notions of the year of jubilee, it became a new and enlightening experience for me. But the Biblical reference is characteristic. A Biblical theologian is at work here. Or when he interprets »Et jævnt og muntert virksomt Liv paa Jord« (A Simple Cheerful Active Life on Earth), bringing Holger Kjær’s memorial article for Ingeborg Appel into the interpretation. In less than no time we are told indirectly that the most precise understanding of what a simple, cheerful, active life on earth is is to be found in Benedict of Nursia’s monastic mle. That, says Allchin, leads us to the question »where we are to place the Gmndtvigian movement in the whole spectmm of Christian movements of revival which are characteristic of Protestantism« (p. 172). Then - in a comparison with revival movements of a Pietistic and Evangelical nature – Allchin proceeds to give a description of a Grundtvigianism which is culturally open, but nevertheless has close affinities with a medieval, classical, Western monastic tradition: a theocentric humanism. »It is one particular way of knitting together the clashing archetypes of male and female, human and divine, in a renunciation of evil and an embracing of all which is good and on the side of life, a way of making real in the frailties and imperfections of flesh and blood a deeply theocentric humanism« (p. 173). Now, there is a magnificent English sentence. And there are many of them. Occasionally some of the English translations make the reader prick up his ears, such as when Danish »gudelige forsamlinger« becomes »meetings of the godly«. I learnt a few new words, too (»niggardliness« and »esemplastic«) the meaning of which I had to look up; but that is only to be expected from a man of learning like Allchin. But otherwise the book is written in an easily understood and beautiful English. This is also true of the large number of translations, about which Allchin himself says that he has been »tantalised and at times tormented« by the problems connected with translating Grundtvig, particularly, of course, his poetry. Naturally Allchin is fully aware that translation always involves interpretation. When for example he translates Danish »forklaret« into »transfigured«, that choice pulls Grundtvig theologically in the direction that Allchin himself inclines towards. This gives the reader occasion to reflect. It is Allchin’s hope that his work on translating Grundtvig will be followed up by others. »To translate Grundtvig in any adequate way would be the work of not one person but of many, not of one effort but of many. I hope that this preliminary study may set in train a process of Grundtvig assimilation and affirmation« (p. 310) Besides being an introduction to Grundtvig, the book also becomes an introduction to past and contemporary Danish theology and culture. But contemporary Danish art, golden age painting etc. are also brought in and interpreted. As a matter of course, Allchin draws on the whole of the great Anglo-Saxon tradition: Blake, Constable, Eliot, etc., indeed, there are even quite frequent references to Allchin’s own Welsh tradition. In his use of previous secondary literature, Allchin is very generous, quoting it frequently, often concurring with it, and sometimes bringing in half forgotten contributions to the literature on Grundtvig, such as Edvard Lehmann’s book from 1929. However, he may also be quite sharp at times. Martin Marty, for example, must endure being told that he has not understood Grundtvig’s use of the term folkelig. Towards the end of the book, Allchin discusses the reductionist tactics of the Reformers. Anything that is not absolutely necessary can be done away with. Thus, what remains is Faith alone, Grace alone, Christ alone. The result was a radical Christ monism, which ended up with undermining everything that it had originally been the intention to defend. But, says Allchin, Grundtvig goes the opposite way. He does not question justification by faith alone, but he interprets it inclusively. The world in all its plenitude is created in order that joy may grow. There is an extravagance and an exuberance in the divine activity. In a theology that wants to take this seriously, themes like wonder, growth and joy must be crucial. Thus, connections are also established back to the great church tradition. It is well-known how Grundtvig received decisive inspiration from the Fathers of the Eastern Church. Allchin’s contribution is to show that it grows out of a need by Grundtvig himself, and he demonstrates how it manifests itself concretely in Grundtvig’s writings. »Perhaps he had a deep personal need to draw on the wisdom and insight of earlier ages, on the qualities which he finds in the sacred poetry of the Anglo-Saxons, in the liturgical hymns of the Byzantine Church, in the monastic theology of the early medieval West. He needs these resources for his own life, and he is able to transpose them into his world of the nineteenth century, which if it is no longer our world is yet a world in which we can still feel at home. He can be for us a vital link, a point of connection with these older worlds whose riches he had deciphered and transcribed with such love and labour« (p. 60). Thus the book gives us a discussion - more detailed than seen before – of Grundtvig’s relationship to the Apostolic Succession, the sacramental character of the Church and Ordination, and the phenomenon transfiguration which is expounded, partly by bringing in Jakob Knudsen. On the background of the often observed emphasis laid by Grundtvig on the descent into Hell and the transfiguration, his closeness to the orthodox form of Christianity is established. Though Grundtvig does not directly use the word »theosis« or deification, the heart of the matter is there, the matter that has been given emphasis first and foremost in the bilateral talks between the Finnish Lutheran Church and the Russian Orthodox Church. But Grundtvig’s contribution is also seen in the context of other contemporaries and reforming efforts, Khomiakov in Russia, Johann Adam Möhler in Germany, and Keble, Pusey and Newman in England. It is one of Allchin’s major regrets that it did not come to an understanding between the leaders of the Oxford Movement and Grundtvig. If an actual meeting and a fruitful dialogue had materialized, it might have exerted some influence also on the ecumenical situation of today. Allchin shows how the question of the unity of the Church and its universality as God’s Church on earth acquired extreme importance to Grundtvig. »The question of rediscovering Christian unity became a matter of life and death« (p. 108). It is clear that in Allchin’s opinion there has been too little attention on this aspect of Grundtvig. Among other things he attributes it to a tendency in the Danish Church to cut itself off from the rest of the Christian world, because it thinks of itself as so special. And this in a sense is the case, says Allchin. »Where else, at the end of the twentieth century, is there a Church which is willing that a large part of its administration should be carried on by a government department? Where else is there a state which is still willing to take so much responsibility for the administration of the Church’s life?« (p. 68). As will be seen: Allchin is a highly sympathetic, but far from uncritical observer of Danish affairs. When Allchin sees Grundtvig as an ecumenical theologian, it is because he keeps crossing borders between Protestantism and Catholicism, between eastern and western Christianity. His view of Christianity is thus »highly unitive« (p. 310). Grundtvig did pioneer work to break through the stagnation brought on by the church schisms of the Reformation. »If we can see his efforts in that way, then the unfinished business of 1843 might still give rise to fruitful consequences one hundred and fifty years later. That would be a matter of some significance for the growth of the Christian faith into the twentyfirst century, and not only in England and Denmark« (p. 126). In Nicholas Lossky’s Afterword it is likewise Grundtvig’s effort as a bridge builder between the different church groupings that is emphasized. Grundtvig’s theology is seen as a »truly patristic approach to the Christian mystery« (p. 316). Thus Grundtvig becomes a true all-church, universal, »catholic« theologian, for »Catholicity is by definition unity in diversity or diversity in unity« (p. 317). With views like those presented here, Allchin has not only introduced Grundtvig and seen him in relation to present-day issues, but has also fruitfully challenged a Danish Grundtvig tradition and Grundtvigianism. It would be a pity if no one were to take up that challenge.